Produksi Material Enrico-Fermi (Memperkaya Kandungan Nitrogen Pada Pupuk Organik Dari Hasil Produk Samping Penyulingan Minyak Nilam) - Novia Arisni; Riana Tania; Izarul Machdar; Umi Fathanah (Fakultas Teknik, 2021)
Utilization of distilled patchouli waste is still very limited, so to optimize it, research is carried out on the manufacture of granule compost from patchouli solid waste trough 3 stages of activity. First aerobic fermentation process of Aceh Jaya patchouli solid waste with variations in the ratio of patchouli solid waste and tofu industrial liquid waste used, namely 1:1; 1:3; and 1:5 then the ratio between waste and bioactivator EM4 is 1:3%; 1:5%; and 1:7%. The second process of Enrico-Fermi fertilizer granulation using granule adhesive, namely tapioca flour with the ratio between Enrico-Fermi fertilizer and adhesive material is 2:1. The three processes of testing the Enrico-Fermi material on patchouli plant growth. The results showed that the highest NPK content in the Enrico-Fermi fertilizer was obtained at the ratio between patchouli waste and tofu liquid waste, namely 1:3 and the addition of EM4 with 7% EM-4 concentrations, namely 5.83% nitrogen, 1.91% phosphorus. and 3.46% potassium. The yield of Enrico-Fermi granule fertilizer was 71.43%. The response of plants to Enrico-Fermi fertilizer resulted in an increase in plant stem height of 5.7 cm, 16 leaves and 3 branches.